2010
DOI: 10.1021/ja103043p
|View full text |Cite
|
Sign up to set email alerts
|

Attomole Detection of Mesophilic DNA Polymerase Products by Nanoparticle-Enhanced Surface Plasmon Resonance Imaging on Glassified Gold Surfaces

Abstract: DNA microarrays are invaluable tools for biosensing applications such as diagnostic detection of DNA and analysis of gene expression. Surface plasmon resonance imaging (SPRI) can detect unlabeled oligonucleotide targets adsorbed to the array elements. The variety of biosensing applications can be expanded by enzymatic manipulation of DNA microarray elements and the sensitivity of detection can be enhanced with the use of oligonucleotide immobilized onto a gold nanoparticle surface (detector-NP). We describe a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 15 publications
0
59
0
Order By: Relevance
“…The side-access effect reported in this study has not been hitherto described, although other investigations demonstrated enzymatic reactions on surface-bound DNA molecules 6,[21][22][23][38][39][40][41][42][43][44] . These studies used either longer dsDNA molecules 23,40 or molecules provided with significantly less-rigid surface linkers and/ or different chemical strategies for DNA self-assembly 6,23,39,41 .…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…The side-access effect reported in this study has not been hitherto described, although other investigations demonstrated enzymatic reactions on surface-bound DNA molecules 6,[21][22][23][38][39][40][41][42][43][44] . These studies used either longer dsDNA molecules 23,40 or molecules provided with significantly less-rigid surface linkers and/ or different chemical strategies for DNA self-assembly 6,23,39,41 .…”
Section: Discussionmentioning
confidence: 45%
“…These studies used either longer dsDNA molecules 23,40 or molecules provided with significantly less-rigid surface linkers and/ or different chemical strategies for DNA self-assembly 6,23,39,41 . Several studies involved ligation enzymes 42,43 , the reactions of which occurred on DNA-binding sites that are readily available on the topmost interface of the matrices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An advantage of the SPR-assisted detection system is the ability to detect amplification products in nontransparent media which, for example, could be potentially useful in monitoring direct PCR amplification from blood [93,94]. A similar SPR detection technique has been utilized for isothermal amplification kinetic monitoring [74,95,96]. …”
Section: Surface Plasmon Resonance Spectroscopymentioning
confidence: 99%